EVALUASI PERTUMBUHAN TINGGI DAN DIAMETER TANAMAN SENGON DENGAN PERLAKUAN BERBAGAI DOSIS PUPUK P SAMPAI UMUR 10 BULAN DI DUSUN JAMBU, KEPUHARJO - , FAJAR KHASANAH; , Ir. Suginingsih, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
MountMerapi, whicheruptedin October 2010resulted inphysicaldamage, chemistry, and biology inthe surroundingareas. Damageoccurred inresidentialas well asagricultural land. Onagricultural land, the landbecomesinfertile. This isbecause ofthe fertiletop soilheatburied in the sandthat can notbe plantedwiththe types ofagricultural cropsandforest trees. Variousplanting activitieshave been carried outinthe affected area. One of theplanting is doneinGuavaHamlet, VillageKepuharjo, Cangkringan, Sleman Districtin May2013sengontypeisplantedwithtreatedmanure applicationandmanureP.Not tobe evaluatedagainstthesengonplant growth, it is necessary toevaluateplant growthto determine theenvironmental improvementgrewafter the eruption. This studyaims to determinethe optimaldose ofPfertilizerforplant growthsengonuntilage10months. Measurementsconductedcensus, conductedsixmonthsafterplanting. Data collection wasperformedwith a gap offourmonths. The parametersmeasuredincludedheight, diameter, andplant death. The results showed thatthe increase in diameteris bestwithmanure applicationandSP36150grams(22.3 mm). The besthighgainiswithmanure applicationandSP3650grams(129.7 cm). Deathsoccurred in thetreatmentplantmanure applicationandSP36150grams.